Pelatihan Pengembangan Aplikasi Mobile untuk Peningkatan Literasi Digital di STMIK Al Muslim Bekasi - Susilo, Arif; Hutauruk, Basar Maringan; Saputra, Alhadi (VIDHEAS: Jurnal Nasional Abdimas Multidisiplin, 2025)
This training aimed to improve the digital literacy of STMIK Al Muslim Bekasi students by mastering the fundamentals of mobile application development. In today's digital era, the ability to develop Android-based applications is a crucial skill that can support graduates' competency and competitiveness in the workforce. The training, conducted in-person and hands-on, covered topics on interface design (UI/UX), basic programming using Android Studio, and publishing applications to digital platforms. Participants were students majoring in Informatics Engineering and Information Systems with an interest in software development. The results of this training demonstrated an increased understanding of mobile application development concepts and basic technical skills in creating and running simple applications. The training also fostered participants' interest in developing digital solutions relevant to community needs. Thus, this activity positively contributes to supporting digital literacy programs within higher education institutions. Keywords: Digital literacy, mobile applications, Android Studio, training, students.